2012
DOI: 10.1002/cbic.201200468
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Activity of the Lipoteichoic Acid Anchor from Streptococcus sp. DSM 8747

Abstract: In this study, the role of lipoteichoic acid (LTA) anchors in the activation of the innate immune response was investigated through the chemical synthesis of a series of LTA derivatives and the determination of their ability to induce NO production in bone marrow-derived macrophages (BMM). To this end, an efficient synthesis of the sn-3-O-(α-D-galactofuranosyl)-1,2-di-O-acylglycerol LTA core was developed, which was then used as a key structure to produce both phosphate and glycerylphosphate-funtionalised LTA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Recently the biological active type 1 LTA from Streptococcus species DSM 8747 has been synthesized by Qiao et al 14. and Sauvageau et al 15. Total synthesis of a derivative of the more complex LTA from S. pneumoniae has also been achieved16 and its interaction with the host immune system revealed that not TLR‐2 but the complement pathway was activated 17.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently the biological active type 1 LTA from Streptococcus species DSM 8747 has been synthesized by Qiao et al 14. and Sauvageau et al 15. Total synthesis of a derivative of the more complex LTA from S. pneumoniae has also been achieved16 and its interaction with the host immune system revealed that not TLR‐2 but the complement pathway was activated 17.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Several unnatural derivatives were synthesized and probed in innate immunological studies to clarify the biological pathway. [13] Recently the biological active type 1 LTA from Streptococcus species DSM 8747 has been synthesized by Qiao et al [14] and Sauvageau et al [15] Total synthesis of a derivative of the more complex LTA from S. pneumoniae has also been achieved [16] and its interaction with the host immune system revealed that not TLR-2 but the complement pathway was activated. [17] Since the structural motive is very different between the families of LTAs, and dependent on the origin, a different biological pathway is not a surprise, but what about other LTAs from other Gram-positive bacteria?…”
Section: Introductionmentioning
confidence: 99%
“…Thus, while compounds 13 [38] and 14 [39] were prepared by treatment with Lewis acids of fully protected precursors and proved to be stable and therefore useful as synthetic intermediates, attempts to prepare compound 15 by treatment with BF 3 ·OEt 2 of the persilylated precursor failed and inevitably led to the anhydro derivative 12 . Moreover, whereas treatment with TFA/THF/H 2 O 90:5:2.5 of 4-nitrophenyl per- O -TBS-α-D-Ara f afforded 16 , 4-nitrophenyl per- O -TBS-β-D-galactofuranoside did not lead to compound 15 under the same conditions and compound 12 was obtained instead (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…DSM 8747 has been synthesized by glycosylation of 9 via the galactofuranosyl iodide, and the method showed to be significantly more efficient than those using traditional glycosyl donors. 28 Condensation of persilylated 9…”
Section: Scheme 2 Synthesis Of 9-decenyl -D-mannopyranoside (3)mentioning
confidence: 99%